The Optimal Defense of Network Connectivity - Dan J. Kovenock; Brian Roberson (Center for Economic Studies and ifo Institute (CESifo), 2015)
Maintaining the security of critical infrastructure networks is vital for a modern economy. This paper examines a game-theoretic model of attack and defense of a network in which the defender's objective is to maintain network connectivity and the attacker's objective is to destroy a set of nodes that disconnects the network. The conflict at each node is modeled as a contest in which the player that allocates the higher level of force wins the node. Although there are multiple mixed-strategy equilibria, we characterize correlation structures in the players' multivariate joint distributions of force across nodes that arise in all equilibria. For example, in all equilibria the attacker utilizes a stochastic `guerrilla warfare' strategy in which a single random [minimal] set of nodes that disconnects the network is attacked.
Keywords: C72; D74; 330; allocation game; asymmetric conflict; attack and defense; Colonel Blotto Game; network connectivity; weakest-link; best-shot